MASALAH-MASALAH SOSIAL DALAM NOVEL TOENGGOEL KARYA EER ASURA - Seha, Nur (ATAVISME, 2008)
Although opus of literature is based on perception process of sociocultural as imaginative, the result of narative construction actually is not only imaginary or fantacy, but also a result of social substances with factual quality. It means that opus of literature takes to the amount of substances the society belief all of them is objective facts. A fact that may be enabled and once happen in society, such as regionalism and nationalism, philosophical and religious, education and emancipation, conflict between youthful and older, tradition and modernization, Western and Eastern and many kind of social contents.